Danhong Injection Price Trend and Its Utilization by Coronary Heart Disease Patients: Evidence From Hospital Records in China - Liu, Liming; Xu, Yue; Su, Zihan; Man, Xiaowei; Jiang, Yan; Zhao, Liying; Cheng, Wei (Frontiers in Pharmacology, 2022)
Background Danhong injection (DHI) accounts for the highest proportion of drug costs for inpatient with coronary heart disease (CHD). However, if DHI price influences utilization remains unclear. Objective To compare changes in the use of DHI for CHD patients during three stages after two comprehensive reforms of public hospitals in Beijing. These findings will provide support for controlling the drug burden of CHD patients and regulating drug use behavior. Research Design CHD diagnosis and treatment data were extracted from the Hospital Information System (HIS) of 33 public hospitals. Patients were grouped according to different treatment methods and clinical classifications. Changes in the utilization of DHI, including the use rate (the percentage of CHD patients using DHI), number of prescribed units (average number of units of DHI prescribed per hospital stay), and cost of DHI per hospital stay (equal to the unit price multiplied by the number of prescribed units) between the three stages were statistically analyzed. Association rules were applied to identify changes in drug combinations. Results After the two reforms, the unit price of DHI dropped from 6.46 to 5.61. At the same time, the use rate increased from 20.77% to 24.00%, the number of prescribed units dropped from 29.76 to 29.21, and the cost of DHI per hospital stay dropped from 192.12 to 163.96. The changes in the use rate and number of prescribed units varied among patients with different clinical types and treatment methods, and the cost of CHI per hospital stay was consistent with the overall situation. The variety of drugs used in combination with DHI remained relatively stable. Conclusion The use rate of DHI for CHD patients increased, indicating increased applications of DHI in clinical practice. Due to the drop in price, the cost of using DHI decreased and the financial burden of this drug was reduced.